Adhering to hand hygiene in Brazilian hospital services: a review study (Research, Society and Development, 2023)
Hand hygiene (MH) is recognized as the most important strategy for reducing cross-transmission of microorganisms in health services. This article aims to evaluate the health professionals' compliance with MH practices in Brazilian hospital services, identify adequacy in relation to the five moments recommended by the World Health Organization, as well as analyze factors that favor and hinder the implementation of this practice. This is an integrative review of the literature. Data collection comprised March 2020 to June 2021. Three categories were analyzed: the support of health professionals to mH practices; hand hygiene and the 5 moments recommended by the WHO and factors that favor and hinder mH. Ten articles that confirmed that the practice of MH in Brazilian hospital services also presented low percentages of support (8.5 to 54.2%). Physicians were the professional category that least adhered to the practice of MH, nurses and physiotherapists the professionals who most sanitize their hands. The moment "after contact" with the patient presented greater adherence. MH is performed preferably with soap and water. Continuing education, posters next to the patient bed, feedback and involvement of leaders are facilitating factors for MH, as well as multimodal interventions. This study shows a low rate of hH support in Brazilian hospital services. The implementation of this practice requires articulation between management policies, as well as scientific knowledge in the construction of a culture for safety in health services.